How EFL Teachers Deal with Pedagogical Competence Development for the Teaching of Writing: A Study on Higher Educational Level in Indonesian Context - Irmawati, Dini Kurnia; Asri, Tri Mega; Aziz, Aulia Luqman (Journal of Education and e-Learning Research, 2021)
This study investigates what has been done by EFL teachers in higher education level or EFL lecturers in the teaching of writing. This study involves seven research subjects who have taught writing for English Department students for at least three years. The data were collected through in-depth interview. The data were then analyzed through open, axial, and selective coding. In relation to development of teaching techniques for teaching writing, the most frequent activity done by the research subjects is to attend workshop and seminar/conference on writing and TEFL (Teaching English as a Foreign Language). The most frequent activity conducted to improve pedagogical competence on material development for writing class is to read literature or article on materials development for writing class from textbook or the internet. As an addition, the most frequent activity the lecturers conducted to develop their pedagogical competence in classroom management is conduct sharing session with fellow and/or senior lecturers. Finally, the most frequent activities the lecturers conducted to improve their pedagogical competence in assessment/evaluation for writing are to read literature or article on ‘assessment/evaluation for writing class’ from textbook, journal, thesis, dissertation, and the internet, and conduct sharing session with fellow and senior writing lecturers and expert in writing. FFuture researchers can develop this study into pedagogical competence in the other English skills (reading, speaking, listening) or other types of competence pivotal for English lecturers (personal, social, and professional). These will have a positive contribution toward development of English as Foreign Language in Indonesian context.